A simple and fast procedure to grow bat fibroblasts from lung biopsies for cytogenetic studies - Morielle-Versute, E. [UNESP]; Varella-Garcia, M. [UNESP] (My University, 1995)
A fast, simple, and inexpensive procedure to establish fibroblast culture from bat lungs is presented. Explants plated following mechanical disaggregation provide good quality preparations for cytogenetics studies in about one week. Cultures established with this procedure may also be used for other biological studies.